Perilaku Pemberian ASI Eksklusif Oleh Ibu Dengan Usia Di Bawah 20 Tahun Di Puskesmas Danau Indah Kec. Cikarang Barat Kab. Bekasi - Nurlina Handarini; Resi Galaupa (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
ABSTRACT:Background: One of the problems with the low coverage of exclusive breastfeeding is the high number of vulnerable teenage mothers who do not have the physical, mental and knowledge readiness to give birth and breastfeed. Age less than 20 years is a period of growth including the reproductive organs (breasts), the younger the mother, the less milk is given. The impact of teenage mothers who do not breastfeed their babies will put their babies at risk of various infectious diseases resulting in less intelligent next generationsResearch objective:. to determine the relationship between behavior and exclusive breastfeeding by mothers under the age of 20 at the Danau Indah Health Center in Kec. West Cikarang Regency. Bekasi in 2023 according to Snehendu B. Kar's theoryType of research:. The research was conducted in March-May. The samples in this study were 30 samples in the Danau Indah Health Center area. This study uses a questionnaire and a list of questions with a quantitative approach method with a cross sectional research design. Purposive sampling techniqueThe results of the study: There is a very good subject behavior that gives exclusive breastfeeding and 2 people breastfeeding while those who behave well by giving exclusive breastfeeding 5 people and those who mix as many as 2 people and formula 5 people and those who have bad behavior exclusive breastfeeding and mix each 2 people and formula 8 peopleResearch conclusion: By testing using the Chi Square statistical test, the value of Ï = 0.032 is obtained, this means that Ï <Î± (0.05) or means that H0 is rejected and Ha is accepted. Thus there is a very good and good behavioral influence on exclusive breastfeedingKeywords: Behavior, Age under 20 years, Exclusive breastfeeding